Swimming pool dermatitis of the fingertips. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
We have already described in the past this dermatitis that can affect simultaneously several subjects attending the same pool so as to suggest an epidemic. In literature there are reports that speak of aggravation of atopic condition induced by the pool; in our patient an aggravation of atopic dermatitis seems unlikely because this never affected her hands and occurred the first time in the summer when perioral atopic dermatitis had regressed; moreover, the dermatitis of our patient had an acute recurrent clinical course that is not characteristic of atopic dermatitis. The sites involved and the severity gradient of the dermatitis in the different fingers support the role played by rubbing the fingertips against the edge of the pool, probably favored by the maceration of the skin in water; this dermatitis affects inexperienced swimming children who cling more often to the edge of the pool.